Uji Antioksidan dan Toksisitas Ekstrak Batang Polygonum Minus Huds Ginjal Tikus Wistar - Sukandiarsyah, Fadli; Ropiqa, Meri; Riska, Bella (Puslitbang Sinergis Asa Professional, 2025)
Kesum plants have demonstrated robust antioxidant activity and possess the potential to function as antiviral, antibacterial, antifungal, anticancer, and antiulcer agents. Further research is necessary to investigate the activity and toxicity of kesum stem preparations. The objective of this study is twofold: first, to ascertain the antioxidant activity of an ethanol extract of kesum stem; and second, to determine the level of acute toxicity in the kidneys of Wistar rats. The extraction process was conducted using the maceration method, employing 70% ethanol as the solvent. The antioxidant activity test demonstrated that the ethanol extract of kesum stem exhibited an IC50 value of 72.03 ppm, thereby classifying it as a strong antioxidant. The acute toxicity test demonstrated that the ethanol extract of kesum stem (Phyllanthus emblica) at doses of 500 mg/kg, 1000 mg/kg, and 2000 mg/kg did not induce toxic effects on the kidneys. This finding was substantiated by the observation that the levels of ureum and creatinine remained within the normal range. The findings of this study, derived from statistical analysis employing the analysis of variance (ANOVA) method, indicated a p-value of 0.632 (p > 0.05) for serum urea examination and 0.06 (p > 0.05) for serum creatinine examination. These findings suggest that there is no statistically significant difference between the treatment groups. The safety of all three doses has been demonstrated by the absence of toxicity effects on rat kidney organs.